Penggunaan Media Gambar dan Alam Sekitar Pada Peningkatan Hasil Belajar IPS Siswa Kelas IV SDN Pudak, Tepus, Gunungkidul - Medi Widodo; Sukadari Sukadari (UM Purwokerto Press, 2022)
The use of learning media is very influential on the learning process. Image media is a form and channel that can be used in the process of presenting information. The natural environment is needed to provide real experience in the learning process. The purpose of this study was to improve social studies learning outcomes on natural features in the local environment for fourth graders at SDN Pudak, Tepus. This research uses classroom action research method. The research subjects were students of class IV SDN Pudak Tepus totaling 8 students, consisting of 3 boys and 5 girls. The data processing procedure is carried out through a flow process consisting of four stages, namely: 1) planning; 2) implementation; 3) observation; 4) reflection. The results showed an increase in student learning outcomes, namely: (1) Pre-cycle, as many as 3 students (37.5%) achieved mastery learning; (2) the first cycle, as many as 6 students (75%) were able to achieve complete learning; and (3) cycle II, as many as 8 students (100%) were able to achieve complete learning. Based on these data, it can be concluded that by using media images and the natural surroundings can improve student social studies learning outcomes.